(untitled) (Journal of Chitwan Medical College, 2021)
Background: Antihypertensive medications reduce blood pressure and decrease cardiovascular disease morbidity and mortality. A number of antihypertensives with same formulation but different prices are available in the market. In the present study we aim to study such price variations of antihypertensive drugs currently available in the Nepalese market. Methods: We obtained the marked price of different antihypertensives manufactured in Nepal and India from various medicine stores within Chitwan from February to June 2021. Cost ratio (CR) and percentage cost variation (%CV) was calculated using Microsoft Office Excel-2019. Results: We observed a high percentage of cost variation in Amlodipine 5mg (CR: 3.33 %CV: 233.33) among Nepali and Losartan 50mg (CR: 32.31 %CV: 3131.47) among Indian antihypertensives. Conclusions: A wide percentage cost variation was observed among antihypertensive medications currently available in the Nepalese market. Regulatory bodies could address the issue to ensure affordability of essential antihypertensive medications.